PERANCANGAN APLIKASI PENJUALAN PAKET WISATA BERBASIS WEB PADA PT FAJAR BUANA TOUR - Natalicia Margatan; Novario Jaya Perdana (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
In the era of information technology development, which is becoming increasingly sophisticated each year, The emergence of advanced technology in the current generation has made B2C e-commerce transactions in Indonesia have experienced positive growth over the years, triggering the online tourism sector to gain major benefits and become one of the main drivers of B2C e-commerce in Indonesia. With the development of today's technology, competition between manufacturers to win the competition is getting tougher significantly. It is the above that builds a sense that in this problem there are opportunities that can be built to solve the problem. The emergence of online travel agents (OTA) in Indonesia makes it more difficult for conventional travellers or other small travellers to compete in marketing their products both domestically and internationally. This is what triggers the emergence of a solution that creates a product for this problem, where the solution is the author wants to make a website-based PT Fajar Buana Tour travel agent, using the prototype method and implementing The 7C Framework guidelines in its manufacture.